THE USE OF A PROJECTIVE TECHNIQUE TO INVESTIGATE THE INTENTION OF KINDERGARTEN STUDENTS IN USING A TABLET PC - Usep Suhud; Sofia Hartati; Widya Pramesti (Jurnal Ilmiah Visi, 2017)
This study aims to measure the impact of social influence on performance expectation, motivation, and attitude, and its implication on intention of kindergarten students to adopt a Tablet PC. In this study, a projective technique was employed. The projective technique is a method used by participants to measure third persons’ behavior. Data was collected in March-April 2016 in Jakarta, involving 210 kindergarten students’ parents. Data was analyzed using an exploratory and structural equation model. Based on the calculation, the Tablet PC adoption intention is affected by performance expectation while performance expectation is affected by social influence. Furthermore, adoption intention is also affected by attitude towards adoption. Recommendations for educators, practitioners, and future study are discussed.